Corporate Social Responsibility Under Authoritarian Capitalism: Dynamics and Prospects of State-Led and Society-Driven CSR. (May 2017) - Hofman, Peter S.; Moon, Jeremy; Wu, Bin
This article introduces the concept of corporate social responsibility (CSR) in the seemingly oxymoronic context of Chinese "authoritarian capitalism." Following an introduction to the emergence of authoritarian capitalism, the article considers the emergence of CSR in China using Matten and Moon's framework of explaining CSR development in terms both of a business system's historic institutions and of the impacts of new institutionalism on corporations arising from societal pressures in their global and national environments. We find two forms of CSR in China, reflecting the "multiplexity" of its business system: one in the mainly family-owned small and medium-sized enterprise sector reflecting concern with local reputation, and another in the corporate, mainly state-owned enterprise (SOE) sector, reflecting global and national societal expectations. We investigate the dynamics of CSR in China through the interplay of the global and national societal pressures and mediating and even leading roles played by the State and the Party. We consider the conceptual integrity and practical prospects for "state-led society-driven" CSR and future research opportunities, including those opened up by the three contributing articles to this special issue.